Precision clinical trials: a framework for getting to precision medicine for neurobehavioural disorders - Lenze, Eric J. (J Psychiatry Neurosci, 2021)
The goal of precision medicine (individually tailored treatments) is not being achieved for neurobehavioural conditions such as psychiatric disorders. Traditional randomized clinical trial methods are insufficient for advancing precision medicine because of the dynamic complexity of these conditions. We present a pragmatic solution: the precision clinical trial framework, encompassing methods for individually tailored treatments. This framework includes the following: (1) treatment-targeted enrichment, which involves measuring patients’ response after a brief bout of an intervention, and then randomizing patients to a full course of treatment, using the acute response to predict long-term outcomes; (2) adaptive treatments, which involve adjusting treatment parameters during the trial to individually optimize the treatment; and (3) precise measurement, which involves measuring predictor and outcome variables with high accuracy and reliability using techniques such as ecological momentary assessment. This review summarizes precision clinical trials and provides a research agenda, including new biomarkers such as precision neuroimaging, transcranial magnetic stimulation–electroencephalogram digital phenotyping and advances in statistical and machine-learning models. Validation of these approaches — and then widespread incorporation of the precision clinical trial framework — could help achieve the vision of precision medicine for neurobehavioural conditions.